RESEÑA DE : De la Sierra Morón, Susana ; Ortiz Pradillo, Juan Carlos (Dirs.). El derecho y la economía ante las mujeres y la igualdad de género . Valladolid : Lex Nova, 2011. - Abad Arenas, Encarnación (Revista de Derecho de la UNED (RDUNED), 2013)
-